Vladimir Putin and Russian statecraft - Lynch, Allen (Washington Potomac Books, 2011)
Since Russian leader Vladimir Putin assumed power in August 1999, speculation about his character, motives, and plans for Russia?s future has been rampant in the West. A portrait of Putin has emerged in the West that is one-dimensional, ill informed, and diametrically opposed to the image of Putin the majority of Russians hold. Even after he stepped down as president in May 2008, retaining a significant measure of power as prime minister under his hand-picked successor, President Dmitri Medvedev, Putin remains poorly understood. In this interpretive biography of Putin, Allen C. Lynch seeks to reconcile the two conflicting images and find out just where the truth lies about the man and the statesman.
Includes bibliographical references and index.
Keywords: Putin, Vladimir Vladimirovich, 1952-